Flexible control of highly‐directive emissions based on bifunctional metasurfaces with low polarization cross‐talking. Issue 5 (10th March 2017) - Xu, He‐Xiu; Tang, Shiwei; Ling, Xiaohui; Luo, Weijie; Zhou, Lei
Abstract : Flexible control on directive emissions toward pre‐designed directions has attracted long‐term interest, but available devices suffer from bulky size, limited functionalities, and low efficiencies. Here, a novel anisotropic meta‐atom exhibiting low polarization cross‐talking was proposed, based on which high‐efficiency metasurfaces with arbitrary polarization‐dependent phase profiles can be easily designed to realize desired beam‐control functionalities. The strategy paves the way to realize high‐performance multifunctional optical devices with high integration. Abstract : Achieving flexible and highly directive emissions toward pre‐designed directions has intrigued long‐held interest in both science and engineering community, but most available efforts suffer the issues of bulky size, limited functionalities, and low efficiency. Here, we propose a general strategy to efficiently and flexibly control the emission beams with dual functionalities realized independently by orthogonal excitations. To overcome the polarization cross‐talking, a novel planar multi‐mode anisotropic meta‐atom is designed by incorporating the screening effect of a surrounding wire loop. As the result, we can design the polarization‐dependent phase profile under certain polarization, without worrying about their influences on the other polarization. As an illustration, two proof‐of‐concept metasurfaces are actualized at microwave frequencies, of which one combines the functionalities of focused‐beam and large‐angle multibeam emissions while another hybrids the functionalities of beam‐steering and small‐angle multibeam emissions. Theoretical, full‐wave simulation, and experimental results are in excellent agreement with each other, which collectively demonstrate the desired performances of our bifunctional devices. Our proposed strategy paves the way to realize high‐performance multifunctional optical devices with high integration and complex wavefront manipulations.